ANALISIS YURIDIS PUTUSAN BAWASLU NOMOR 02/REG/L/TSM- PW/08.00/XII/2020 TENTANG DISKUALIFIKASI TERHADAP PEMENANG PEMILIHAN KEPALA DAERAH KOTA BANDAR LAMPUNG - Bunga Salsabila; Dessy Artina; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Indonesia is a constitutional state that adheres to democracy and a system ofgovernment based on people's sovereignty. The most substantial understanding of democracyis general election (election). Elections are a means to elect people's representatives who willcontrol the wheels of government. Elections are held by the General Election Commission(KPU). KPU is domiciled at the center or in the regions. The KPU at the regional level istasked with holding elections at the regional level, one of which is the Regional Head Election(Pilkada). So far, the Pilkada implementation has been inseparable from the obstacles andchallenges that have occurred. Starting from the implementation, as well as violationscommitted by the candidates themselves. So that maximum supervision and monitoring isneeded by Bawaslu. One of the Pilkada problems that occurred in Bandar Lampung City,Lampung Bawaslu stated that Candidate Pair serial number 03, Eva Dwiana-DeddyAmarullah had been proven to have violated the Structured, Systematic, MassiveAdministration (TSM) in the 2020 Bandar Lampung Pilkada, so that this pair was canceledfrom participating in the Bandar Lampung Pilkada.This research belongs to the normative juridical, namely research conducted byexamining secondary legal materials or research based on standard rules that have beenrecorded and discusses legal principles and synchronization. The data sources used areprimary data, secondary data and tertiary data with library research data collectiontechniques.The research results obtained, should The Supreme Court as the first legal remedy inmaking a decision must review the legality of letters or policies issued by KPU BandarLampung and be considered by judges in canceling election results, because they canendanger democracy and damage the morality of voters in Bandar Lampung City in thefuture. Then for the Arrangement of Bawaslu Authority in receiving violations of TSMreportsthere must be a systemreinforcement of the Bawaslu with the actions of the Bawaslu indeciding a dispute the process is final. This is done in order to maximize the implementationof authorityquasi-judicial, in the form of an adjudication function so that Bawaslu can decideon election administration violations, decide on money politics violations, and electionprocess disputes without further appeals.Keywords: Election, Bawaslu, Pilkada